After State Repression: Movement Abeyance in Hong Kong under the Enforcement of the National Security Law. (February 2023) - Kwong, Ying-Ho
The Chinese government has imposed the National Security Law which has resulted in Hong Kong formally entering into a phase of movement abeyance. By analysing 3377 posts on LIHKG Internet forum, this article re-explores the online protest attitude during this movement abeyance. The findings indicate that content creators are more attentive in regard to criticizing the legislation and pro-Beijing figures, followed by seeking international support and calling for unity. Users are more 'participative' in calling for mutual destruction between the authorities and people, initiating mutual support and seeking emigration. This study provides new perspectives on the study of movement abeyance.